All is not forgotten - Walker, Wendy , 1967- (HarperCollins, 2017)
"In the small, affluent town of Fairview, Connecticut, everything seems picture perfect. Until one night when young Jenny Kramer is attacked at a local party. In the hours immediately after, she is given a controversial drug to medically erase her memory of the violent assault. But, in the weeks and months that follow, as she heals from her physical wounds, and with no factual recall of the attack, Jenny struggles with her raging emotional memory. Her father, Tom, becomes obsessed with his inability to find her attacker and seek justice while her mother, Charlotte, prefers to pretend this horrific event did not touch her perfect country club world. As they seek help for their daughter, the fault lines within their marriage and their close-knit community emerge from the shadows where they have been hidden for years, and the relentless quest to find the monster who invaded their town - or perhaps lives among them - drive this psychological thriller to a shocking and unexpected conclusion"